Effectiveness of calcium chloride in reduction of shoot necrosis incocoa (Theobroma cacao L.) in vitro propagation - Sulistyani Pancaningtyas (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2012)
Various efforts have been developed for the optimization of the various stages in vitro micropropagation. The maturation stage and pre-acclimatization plantlets is an important stages that must be considered to produce vigorous plants and ready to be planted in the field. The purpose of this study was to reduced shoot tip necrosis in cocoa planlets to obtaine vigorous planlets from in vitro propagation through the addition of Calcium Chloride (CaCl2). The study used two stages of embryogenic development. The first was embryo maturation stage and the second was the shoot growth development stage. The study was arranged factorially in experiment design of Completely Randomized Design consisting of two factors i.e. concentration of CaCl2 consisted of 0, 50, 100, 150, and 200 mg/l and clones consisted of Sulawesi 1 and Sca 6. Each experiment was repeated three times, so the number of combination trials were 5x2x3=30 experimental units. The parameters observed included shoot growth percentage and vigorous planlets percentage. The results showed that the addition of CaCl2 at a concentration of 150 mg/l during maturition stage increased the embryos performance and percentage of shoot tip. However, it could not prevent the shoot tip necrosis. Whereas, the addition at a concentration of 50 mg/l during the shoot m growth development stage could reduced necrosis, suggested to increase the quality of in vitro planlets.Key words: Cocoa, necrosis, calcium chloride, somatic embryogenesis, embryos, planlets, in vitro.